The Development of Biology Interactive Learning Media Based Macromedia Flash in the Material of Digestive System of Human at Class XI SMA/MA - Harahap, Hasmi Syahputra; Hasruddin, Hasruddin; Djulia, Ely (Universitas Sebelas Maret, 2015)
This study aims to determine: (1) The expedience degree of Biology interactive learning media based macromedia flash; (2) The responses of SMA Biology MGMP teachers; and (3) The responses of students as to Biology interactive learning media based macromedia flash in the material of Digestive System of Human at class XI SMA/MA. This development study which stages includes are: (1) Collect to information; (2) Planning (preparing benchmark reference test); (3) To develop an early form of product; (4) Validation of expert; (5) Revision; (6) Test final product; and (7) Revision of the eligibility of product. The test subject consists of validator in material experts, language expert, and learning design media experts, and one MGMP teacher with 36 students in MAN 1 Medan on small group trial, four MGMP teachers with 85 students in MAN 1 and MAN 2 Model Medan on middle group trial, and then nine MGMP teachers with 165 students in MAN 1, MAN 2 Model, and MAN 3 Medan on large group trial. Data collected by using a questionnaire. Data analyzed with descriptive quantitative and qualitative techniques. The results of this study showed that: (1) The Eligibility material content is in very good criteria (88%); (2) The Language of learning media is in very good criteria (85%); (3) The Media development product is in very good criteria (84%); (4) The responses of one MGMP teacher is in helping criteria (4,1) and 36 students are in very good criteria (82%); (5) The responses of four MGMP teachers are in very helping criteria (4,3) and 85 students are in very good criteria (82%); and (6) The responses of nine MGMP teachers are in very helping criteria (4,7) and 165 students are in very good criteria (84%).Keywords: Macromedia Flash, Digestive System of Human, Questionnaire, Descriptive Quantitative, and Qualitative.